DUTA MERK, CITRA MERK DAN PEMASARAN SOSIAL MEDIA TERHADAP KEPUTUSAN PEMBELIAN SKIN CARE MS GLOW - Irawati, Rina (Jurnal Manajemen dan Profesional, 2024)
The need for women to maintain their appearance through beauty and health has driven the growth of beauty products today. The aim of the research is to test the influence of brand ambassadors, brand image, social media marketing on purchasing decisions for MS Glow in Malang. Sampling used the Malhotra technique with 75 respondents. The analysis method uses simple regression. All variable items are declared valid and reliable. The assumption test results show that it is free from multicollinearity, heteroscedasticity, normal and linear distribution. The results of testing the research hypothesis showed that there was a partial positive and significant influence between brand ambassadors on purchasing decisions for MS Glow skincare products (sig. 0.011 < α 0.05). There is a positive and partially significant influence between brand image on purchasing decisions for MS Glow products (sig. 0.003 < α 0.05). There is a positive and partially significant influence between Social Media Marketing on purchasing decisions for MS Glow products (sig. 0.003 < α 0.05). Social Media Marketing (X3) has a dominant influence on purchasing decisions with the highest beta value of 0.426. Research findings are supported by research by Ramadhani (2023), Punjungawidya (2022), Marliya (2023), Amin (2021), Brestilliani (2020), Sagir (2021), Liya (2021), Paramita (2021), Sagia (2018), Arianty (2021), Liya (2021), Paramitha (2021), and Putra (2022). Paramitha (2021), and Putra (2022).